Improved meet-in-the-middle attack on Joltik-BC-128 - LI Zheng; REN Jiongjiong; LI Manman; CHEN Shaozhen (网络与信息安全学报)
The Joltik-BC, adopting the substitution-permutation network structure and Tweakey framework, was a lightweight tweakable block cipher published at ASIACRPYPT 2014. By researching the internal characteristic of the Joltik-BC, a 6-round meet-in-the-middle distinguisher against the Joltik-BC-128 was constructed by controlling the tweakey differentials and combining differential enumeration and differential characteristics of S-boxes. An improved meet-in-the-middle attack against the 9-round Joltik-BC-128 was developed using this distinguisher. The memory and time complexities of the improved 9-round Joltik-BC-128 were 244.91 64-bits blocks and 248 9-round Joltik-BC-128 encryptions. Compared with existing meet-in-the-middle attack results, the time complexity and memory complexity of this method were significantly reduced.